Predictive models for adverse clinical outcomes in Chinese patients with atrial fibrillation undergoing percutaneous coronary intervention with stenting. Issue 4 (21st April 2022) - Zheng, Jian-Yong; Cao, Yi; Li, Dong-Tao; Qiu, Yi-Gang; Zhao, Li; Xu, Zheng-Ming; Huang, Yi-Xiong; Hong, Zhi-Bo; Li, Tian-Chang; Tang, Yi-Da; Guo, Cheng-Jun; Ma, Zhi-Min; et al.
Abstract: Objective: This study aimed to evaluate predictors for adverse cardiovascular outcomes in patients with atrial fibrillation (AF) undergoing coronary stenting. Methods: We retrospectively recruited consecutive patients with previously documented non-valvular AF who underwent coronary stenting between January 2010 and June 2015 in 12 hospitals of Beijing, China. Major adverse cardiac/cerebrovascular events (MACCE) were a composite of all-cause death, non-fatal myocardial infarction, repeat revascularization, and ischaemic stroke/systemic thromboembolism (IS/STE). Major bleeding referred to grade 2 or higher of Bleeding Academic Research Consortium criteria. Results: A total of 2394 patients (men: 72.3% vs. women: 27.7%, median age: 67 years) were included. The CHA2 DS2 -VASc and HAS-BLED were 3.6 ± 1.6 and 1.9 ± 0.7, respectively. The median follow-up duration was 36.2 months. There were 230 (9.6%) deaths, 96 (4.0%) IS/STE, 426 (17.8%) MACCE, and 72 (3.0%) major bleeding. Multivariate Cox regression yielded predictive models for (1) all-cause death: diabetes, prior myocardial infarction, chronic kidney disease (CKD), ST-segment elevation myocardial infarction (STEMI) at presentation, heart failure, no use of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, and statins; (2) IS/STE: advanced age, prior history of ischaemic stroke and intracranial haemorrhage; (3) MACCE: prior history of myocardial infarction and ischaemic stroke, CKD, STEMI, heart failure, and no statin use; (4) major bleeding: prior major bleeding, prior myocardial infarction, CKD and use of oral anticoagulants. Conclusion: Chinese patients with AF and coronary stenting had high mortality and incidence of MACCE. We compiled separate predictive models for all-cause death, IS/STE, MACCE, and major bleeding.